The undiscovered mind how the brain defies explaination - Horgan, John (Weldenfeld & Nicolson, 1999)
"Is Horgan's new prophecy of doom intended to announce the beginning of the end for the mind and brain sciences, or to dare us to achieve the goal he says we can't? The Undiscovered Mind is usually fun, sometimes infuriating, but never dull."